IMPLEMENTING STIMULATION OF CHILDREN'S WRITING ABILITY OF 4-5 YEARS OLD BY DRAWING IN BA 'AISYIYAH YANGGONG JENANGAN PONOROGO - Paryanti Paryanti; Betty Yulia Wulansari; Sidik Nuryanto (EDUPEDIA, 2018)
The purpose of this study was to describe and explain the process of stimulating the writing ability of children aged 4-5 years by drawing in BA 'Aisyiyah Yanggong Jenangan. Knowing the supporting factors and inhibitors of the implementation of stimulation when writing by drawing. This type of research is descriptive qualitative research, carried out in BA 'Aisyiyah Yanggong Jenangan. The subjects of this study were group A students, amounting to 10. Principals and group A teachers as informants. The object of this study is the implementation of stimulation of the ability to write children aged 4-5 years by drawing. Data collection methods used in this study are interviews, observation and documentation. To check the validity of the data using the method and source triangulation techniques. Data analysis techniques using the Miles and Huberman models, the steps taken are data collection, data reduction, data presentation and conclusion drawing. Stages of the implementation of stimulation of the ability to write children aged 4-5 years by drawing in BA 'Aisyiyah Yanggong Jenangan, as follows: The first stage of a child's groom is a random graffiti. The second stage of a child's picture resembles a letter. The third stage the child makes pictures and writes the initial letter. The fourth stage the child can write his own name and mimic writing words. Supporting factors in the implementation of stimulation of writing ability by drawing: the teacher masters the learner writing method by drawing so that it can develop children's writing skills, availability of media and complete equipment in the institution. Inhibiting factors in the implementation of stimulation of writing ability by drawing, including: Children lack concentration when learning, there are children who do not want to follow learning and prefer to play, parents are less facilitating of learning equipment.